STRATEGI MANAJEMEN KONFLIK KEPALA RUANG DENGAN PRODUKTIVITAS KERJA PERAWAT DI RUANG RAWAT INAP RUMAH SAKIT TINGKAT III BALADHIKA HUSADA JEMBER: Conflict Management Strategy of the Head Room with Nurse Work Productivity in the Inpatient Room of Level III Baladhika Husada Jember Hospital - Kadek Fadila Oktaviana; Asmuji; Dwi Yunita Haryanti (Forind Press, 2024)
Conflict is one of the things that can affect work productivity, conflict can have a positive or negative impact depending on how it is handled. In the scope of nurses in the hospital, the head of the room becomes one of the important roles in resolving conflicts in nurses. The purpose of this study was to determine the relationship between conflict management of the head of the room with the work productivity of nurses in the inpatient room of Level III Baladika Husada Jember Hospital. This research design is a correlation with a cross sectional approach. The population of this study were 78 nurses in the inpatient room. The sample of this study amounted to 63 nurses. The sampling technique used was probability sampling by means of proportionate stratified sampling. The instrument in this study was a questionnaire. From the research it was found that conflict management was good (90.5%), conflict management was sufficient (9.5%), good work productivity (73%), sufficient productivity (27%). The results of the Spearman's Rho statistical test with (ɑ = 0.05) showed a p value of 0.021 so that H1 was accepted, which means that there is a relationship between the conflict management of the head of the room with the work productivity of nurses in the inpatient room of Level III Baladhika Husada Jember Hospital with a weak relationship strength (r = 0.290). Good conflict management from the head of the room plays an important role in creating a comfortable environment so that it can increase the work productivity of nurses.